Análisis de la recaudación tributaria del impuesto a los consumos especiales (ICE) a las fundas plásticas y su relación en el consumo de las mismas en el cantón de Latacunga, provincia de Cotopaxi, periodos 2020 al 2022. - Ñato Lanchimba, Giovanna Lizbeth (2023)
This research project aims to analyze the tax collection of the Special Consumption Tax (ICE) on plastic bags and the relationship in the consumption of plastic bags in the canton Latacunga, province of Cotopaxi during the years 2020 to 2022, a period in which Resolution No. NAC-DGERCGC20-00000033 was in force, which provided for the gradual increase of the tax. The methodology had a quantitative approach, due to the fact that data collection was performed, that is, measurable data to formulate facts, through a database of the SRI on the income received by ICE on plastic bags. The type of research was conducted in a documentary, descriptive, and explanatory way to help better understand this project. Within the population, we considered the companies that are within the ISIC 4.0 class G4630 and G4711 of the Latacunga canton. As a result, it was identified that the collection of the tax in the period from 2020 to 2021, presented an increase, being that in 2020 the collection was $2,536.42 and in the year 2021 of $3,637.26, presenting a variation of 43.40%, in the following periods a decrease in the collection was identified for a value of $831.11, which represents that people become more aware of the environment and change their consumption habits, taking into account that during the year 2022, the tax per plastic bags was $0.08. Within what is The acquisition and consumption of plastic bags by companies have a significant relationship since the trend is that the more plastic bags are acquired, the more taxes will increase.